Periodontal Status of Tuberculosis patients - Inter linked with each other - Ziaulhaq Shahzad, Farah Ahmad, Syed Hasan Danish, Shahid Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Evidence suggests periodontitis may contribute to the development and progression of respiratory illnesses. However, few studies currently look at the coexistence of periodontitis and tuberculosis. The current study investigates the relationship between periodontal health and tuberculosis. Aim: To assess various clinical dental parameters of periodontal health among patients with and without TB. Methods: The participants in the present case-control study were individuals who obtained informed permission forms to participate when they were patients in the outpatient dentistry department. The current study included 585 patients in total. Three hundred-one individuals with normal pulmonary function were added to the control group, whereas 284 patients with tuberculosis were added to the cases group. The diagnosis of the pulmonary conditions was confirmed using spirometry. Using SPSS software 21, we evaluated the demographics & clinical indicators such as plaque, different gingival parameters of periodontitis, Gingival bleeding, and gingival index (GI), and compared cases and controls. Results: The population comprised two hundred eighty-seven women (49.1%) and 298 men (50.9%). There was a significant association between tuberculosis and periodontitis, and it has been observed that 159 (56%) tuberculosis patients had 6.23 (4.2 – 9.1) times higher effects on oral periodontitis issues (P<0.001*). Patients with gingivitis had a significantly higher number of bleeding, accounting for 241 (72.8), p<0.001. Practical implication: The study suggests that healthcare providers, particularly those involved in the treatment of TB, should consider incorporating oral health screening and assessment as part of the overall care for TB patients. This could help identify and address periodontal issues that may exist, hence dental professionals can play a role in the early detections of TB Conclusion: This study suggest that important relationship between TB and periodontitis. TB patients should be educated about the potential impact of their disease on periodontal health and encouraged to maintain regular dental visit and oral hygiene. Keywords: Tuberculosis (TB), Periodontitis (PD), Gingival bleeding, and gingival index (GI)